Pengenalan Budaya Indonesia Melalui Permainan Berbasis Android - Victorio Nasution, Anang Kukuh Adisusilo, Beny Yulkurniawan (SMATIKA, 2014)
The younger generation is more interested to know the culture of other nations than our own nation.Sense of pride in their own culture, have faded and considers culture in Indonesia is ancient and outdmodedso be reluctant to know more about the national culture. Technological developments in the information isnow widespread in various fields, both in the services sector, the banking industry, as well as on the field ofgame. The game is now preferred by the younger generation so that it can be a means to introduceIndonesian culture, the factors that can be used for socialization and learning process [1] about the cultureof Indonesia.Â Â The game can be played anywhere by using mobile-based technology, it is more interesting for the userto use the game. Mobile technology that is widely used and is free to use android. A variety of Indonesianculture such as weapons, clothing, and other custom homes to show identity and national character can becreated for a game application that is expected to be one means to introduce the culture and history of theIndonesian culture so favored by the younger generation in particular, and society in general. Games withIndonesian cultural features examined in this research, by taking various cultural elements such asMajapahit culture and puppets. The character look like the snails with a Bagong face and Dragon Antabogaas Non Player Character.